DESIGNING ANDROID-BASED LED TELEVISION FOR DETECTING DAMAGE USING FORWARD-CHAINING METHOD - Imam Fatoni; Fitria Fitria (Proceeding International Conference on Information Technology and Business, 2020)
LED television (Light Emitting Diode) was the digital display technology that generated images on a flat surface with a lighting system through LED backlight technology. In terms of quality and technology, LED television was also highly developed because LED television was free from damage. The problem statement of this study was that detecting damage on LED television was not easy for newly-experienced technicians e.g., vocational students and apprentices who had just finished the training on television reparation at Al- Mubarok Electronic Service. It was because of a lack of their knowledge and experience in detecting damage to LED televisions so that they needed a system for consulting the experienced technicians and the training spots. The system was built through Expert System Application by using the Forward Chaining method that was able to interfere the engine uses – the user-defined information to move to AND and OR logic – until an object was determined. All rules must be met so that an object was achieved. This system was made through Android so that it was able to be used anytime and anywhere. The result of this study was the implementation of the LED television damage detection system using the Forward Chaining method. It was expected that the system or application that had been created provided convenience in the initial detection process for technicians or users.Keywords: LED Television, Expert System, Forward Chaining, Android